Transcriptome profiling of a spirodiclofen susceptible and resistant strain of the European red mite Panonychus ulmi using strand-specific RNA-seq. (December 2015) - Bajda, Sabina; Dermauw, Wannes; Greenhalgh, Robert; Nauen, Ralf; Tirry, Luc; Clark, Richard; Van Leeuwen, Thomas
Abstract Background The European red mite, Panonychus ulmi, is among the most important mite pests in fruit orchards, where it is controlled primarily by acaricide application. However, the species rapidly develops pesticide resistance, and the elucidation of resistance mechanisms forP. ulmi has not kept pace with insects or with the closely related spider miteTetranychus urticae . The main reason for this lack of knowledge has been the absence of genomic resources needed to investigate the molecular biology of resistance mechanisms. Results Here, we provide a comprehensive strand-specific RNA-seq based transcriptome resource forP. ulmi derived from strains susceptible and resistant to the widely used acaricide spirodiclofen. From ade novo assembly of theP. ulmi transcriptome, we manually annotated detoxification enzyme families, target-sites of commonly used acaricides, and horizontally transferred genes implicated in plant-mite interactions and pesticide resistance. In a comparative analysis that incorporated sequences available forPanonychus citri, T. urticae, and insects, we identified radiations for detoxification gene families following the divergence ofPanonychus andTetranychus genera. Finally, we used the replicated RNA-seq data from the spirodiclofen susceptible and resistant strains to describe gene expression changes associated with resistance. A cytochrome P450 monooxygenase, as well as multiple carboxylcholinesterases, were differentially expressed between the susceptible and resistant strains, and provide a molecular entry point for understanding resistance to spirodiclofen, widely used to controlP. ulmi populations. Conclusions The new genomic resources and data that we present in this study forP. ulmi will substantially facilitate molecular studies of underlying mechanisms involved in acaricide resistance.